Case Study: Combination of Ankle Pump Exercise and 30° Elevation in Foot Edema in Patients with Chronic Kidney Failure - Gusty, Reni Prima; Rivaldi, Fahri; Harni, Siti Yuli (Universitas Padjadjaran, 2025)
Edema is a common complication in patients with chronic kidney disease (GGK) caused by fluid retention and electrolyte imbalance, leading to discomfort, limited mobility, and reduced quality of life. Non-pharmacological interventions such as a combination of ankle pump exercise and 30° leg elevation are known to reduce edema by improving venous and lymphatic return. This study aimed to determine the effectiveness of combining ankle pump exercise and 30° leg elevation in reducing the degree of edema in GGK patients. This case study employed an Evidence-Based Nursing (EBN) approach involving two GGK patients in the Male Internal Ward of RSUP Dr. M. Djamil Padang. The intervention patient received a combination of ankle pump exercise and 30° leg elevation along with pharmacological therapy (furosemide), while the control patient received only standard pharmacological therapy. The intervention was conducted for four consecutive days, three times daily, for 30 minutes per session. The degree of edema was assessed using the pitting edema method by Brodovicz before and after the intervention. The results showed a reduction in edema degree from degrees 3 to degrees 2 in the intervention patient, while the control patient experienced an increase from degrees 3 to degrees 4. This finding indicates that the combination of ankle pump exercise and 30° leg elevation effectively reduces edema through calf muscle contractions that promote venous return and gravitational effects that lower hydrostatic pressure in the lower limbs. This intervention is safe, inexpensive, easy to perform, and can be integrated into daily nursing practice. In conclusion, the combination of ankle pump exercise and 30° leg elevation is an effective, evidence-based, non-pharmacological nursing intervention to reduce the degree of edema in GGK patients and can serve as an alternative to improve patient comfort. Keywords: Chronic kidney disease, edema, ankle pumping exercise, 30° leg elevation.